Comparative analysis of cultural elements in the fairy tales of “Timun Mas” and “Momotaro” - Ramadhani, Anis Kusuma; Rachmawati, Enna; Siagian, Irwan (Japanese Research on Linguistics, Literature, and Culture, 2021)
This study aims to analyze and describe the comparison of cultural elements found in the Indonesian fairy tale "Timun Mas" and the Japanese fairy tale "Momotaro". This research is a comparative literature study. This study uses qualitative research methods with a comparative literature approach and Koentjaraningrat theory to compare the cultural elements contained in the two fairy tales. The data source is a collection of folklore books, including the Timun Mas fairy tale and the Japanese "Momotaro" http://kursus-jepang-evergreen.com/index.php/cerita-dongeng-jepang/63-momotaro The study found differences and similarities in the cultural elements of the Timun Mas fairy tale and the Momotaro fairy tale. Of the seven elements of culture, five similarities were found, namely the elements of the religious system and religious ceremonies, social systems and organizations, knowledge systems, livelihood systems, and technology and equipment systems. In comparison, the difference lies in the elements of language and art.